2023
DOI: 10.1007/s12187-023-10016-2
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Lived Experiences of Wellbeing at School in England: a Phenomenological Inquiry

Abstract: This phenomenological inquiry investigated children’s wellbeing experiences at school, including their hedonic (feeling good) and eudaimonic (doing good) accounts, a distinction often overlooked. Further, while phenomenological inquiries of children’s mental ill-health exist, wellbeing, a fundamental part of mental health, is neglected. This is at odds with positive psychology which favours strengths-based approaches to studying human development. Phenomenology provides rich detail, facilitating deeper underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…• What does 'doing well' at school mean to adolescents? Both quantitative and qualitative project phases were pre-registered via the Open Science Framework (Clarke & McLellan, 2022a, 2022b.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…• What does 'doing well' at school mean to adolescents? Both quantitative and qualitative project phases were pre-registered via the Open Science Framework (Clarke & McLellan, 2022a, 2022b.…”
Section: The Present Studymentioning
confidence: 99%
“…The impact of high‐stakes testing on children's wellbeing is a long‐standing concern in England and internationally (Brown & Dixon, 2019; Cho & Chan, 2020), with pupils as young as nine experiencing academic performance as indicators of self‐worth (Clarke & Platt, 2023; Reay & Wiliam, 1999). It is argued that England's performativity culture (Ball, 2003) utilising judgements and comparison to control and incentivise, undermines children's wellbeing (Navarro et al, 2017; Roome & Soan, 2019), especially eudaimonia.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Such cultures often undermine children's wellbeing (Ryan & Weinstein, 2009) and whole-child approaches to education. Indeed, research suggests performativity cultures can breed a fixation with academic attainment and competition among children (Clarke & Platt, 2023; Hargreaves et al, 2022). As a result, there is a tension between English schools’ responsibilities to (1) care for children's wellbeing, now part of statutory curricula (Department for Education, 2019b), and (2) ensure pupils achieve increasingly high academic standards (Department for Education, 2022).…”
Section: Theoretical Overviewmentioning
confidence: 99%
“…This study was part of a larger mixed multi-method research project investigating children's and adolescents’ wellbeing and academic attainment at schools in England (see Clarke, 2023; Clarke & Hoskin, 2022; Clarke, McLellan & Harold, 2023; Clarke & Platt, 2023, also detailed in Supplementary Materials). The present article documents the quantitative findings from the Primary school (ages 9–11) phase, a cross-sectional study which seeks to extend research on the wellbeing-attainment association in three main ways.…”
Section: The Current Studymentioning
confidence: 99%
“…Focusing on schools is relevant considering recent research showing that schools serve as influential environments where children spend much formative time and which influences the development of academic and personal skills (Malik & Shujja, 2013). Additionally, understanding children's happiness and wellbeing is vital to develop policies and practices to promote a holistic development at schoolsnot merely academic (Clarke & Platt, 2023). Considering recent research around subjective wellbeing in young children, it has been shown that recognising success beyond academic achievement fosters eudemonic wellbeing (Losada-Puente et al, 2022).…”
mentioning
confidence: 99%